Deciphering the virulence factors, regulation, and immune response to Acinetobacter baumannii infection - Shadan, Afreen; Pathak, Avik; Ma, Ying; Pathania, Ranjana; Singh, Rajnish Prakash (Frontiers in Cellular and Infection Microbiology, 2023)
Acinetobacter baumannii is a gram-negative bacterial pathogen that has been considered an important pathogen due to the increasing number of infections over the preceding three decades and shows resistance to multiple antibiotics. This human pathogen is responsible for infections in hospital settings, clinical sectors, ventilator-associated pneumonia, and bloodstream infections which lead to mortality rates up to 35%. With the development of advanced genome sequencing, molecular mechanisms of manipulating bacterial genomes, and animal infectious studies, it has become more convenient to identify the factors that play a major role in A. baumannii infection and persistence. In the present review, we have explored the mechanism of infection, virulence factors, secretion systems, outer membrane proteins, and various other factors associated with the pathogenesis of this organism. Additionally, the role of the innate and adaptive immune response and the current progress in the development of innovative strategies to combat this multi-drug-resistant pathogen is also discussed.